PENGARUH PENGGUNAAN SODIUM BIKARBONAT PADA ANESTESI BENIH IKAN GURAMI (Osphronemus gouramy, Lac.) TERHADAP LAMA WAKTU INDUKSI DAN PEMULIHAN KESADARAN - Irhami, Irhami; Rahmayanti, Fitria; Muliyana, Agusriati; Munandar, Munandar (Universitas Teuku Umar, 2023)
Anesthesia is an activity commonly performed in aquaculture to reduce stress on fish seeds during transportation or for other routine handling. Sodium bicarbonate is an anesthetic agent that has been used in aquaculture on several types of fish, but has not been tested on gouramy (Osphronemus gouramy, Lac.). This study aims to determine the effect of using sodium bicarbonate in anesthesia of gouramy seeds. This study was an experimental study using a completely randomized design with four treatments and three replications for each treatment, namely treatment A (without adding sodium bicarbonate), B (5 g/L), C (10 g/L), D (15 g/L) and E (20 g/L). The results showed that sodium bicarbonate could be used as an anesthetic agent for gouramy seeds with the best dose in treatment E (20 g/L). In treatment E (20 g/L), the induction time for gouramy seeds was very sort, less than 3 minutes. Fast induction time could prevent stress on the fish due to anesthesia.